Popularizing Philosophy: Learning Construction in the Perspective of Metacognitive Theory - In’am Esha, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
This article aims to conduct a study of the learning construction of philosophy in the perspective of metacognitive theory. Learning development construction in metacognitive perspective has five stages: (1). Student Awareness Development Stage, (2). Learning Planning Stage, (3). Learning Results Information Management Stage, (4). Learning Results Monitoring Stage, and (5). Evaluation Stage. Based on the framework of these stages, this study found that philosophy learning is carried out using the principles and stages of learning: Building Positive Awareness for Philosophy; Developing philosophy learning skills; Managing information in the philosophy learning process; Monitoring the philosophy learning results; and Evaluation of the philosophy learning results.